Antisemitism on the Rise : The 1930s and Today - Steinacher, Gerald; Kohen, Ari, 1977- (Book collections on Project MUSE., 2021)
"A collection of historical and contemporary research and essays, Antisemitism on the Rise: the 1930s and Today evaluates the progression of antisemitism from the interwar period to today and provides examples for how to effectively teach current research and antisemitism as a whole"--